Conflict resolution in Asia mediation and other cultural models - Stobbe, Stephanie Phetsamay (Lanham Lexington Books, 2018)
"Examines the role of mediation and other cultural conflict resolution models in Asia. the contributors use various countries as case studies to analyze how traditional, Indigenousenous, and culturally based conflict resolution processes interact with more formal legal systems to address conflicts" --Provided by publisher
Introduction : conflict resolution and peacebuilding in Asia : the need for mediation and other culturally appropriate models / Stephanie P. Stobbe -- Indonesia : the role of the traditional, Indigenous musyawarah mufakat process of mediation / Fatahillah Abdul Syukur and Dale Bagshaw -- Laos, op-lom : the language of conflict resolution and mediation models / Stephanie P. Stobbe -- Philippines : traditional peacemaking processes among Indigenous populations in the northern and southern Philippines / Bruce E. Barnes and Federico V. Magdalena -- Thailand : Thai cultural values and the role of third parties in addressing conflicts / Vanchai Vatanasapt and Stephanie P. Stobbe -- Singapore : cultural influences in the historical and institutional development of mediation / Joel Lee -- Vietnam : culturally and legally appropriate mediation for dispute solution in Vietnam / Charles W. Crumpton -- China (mainland) : the gong hui mediation committee, ju wei hui neighborhood committee, he shi lao peacemaker, and other cultural models of conflict resolution / Eko Yi Liao and Cheryl Qianru Zhang -- Hong Kong : mediation and the future of dispute resolution / Nadja Alexander -- India : Panchayats mediation and Lok Adalat People's Court conciliation, and the institutionalization of ADR / Geetha Ravindran -- Conclusion : common principles and practices found Conflict resolution in Asia: mediation and other cultural models and the future of mediation and cultural practices of conflict resolution and peacebuilding / Stephanie P. Stobbe.
Includes bibliographical references and index.
Keywords: Dispute resolution (Law); Conflict management -- Asia; Mediation -- Asia; Peace-building -- Asia